Strategi Penanggulangan Tindak Pidana Narkotika oleh Anak di Era Digital - Clarina, Revi; Monica, Dona Raisa; Maulani, Diah Gustiniati (Indonesian Journal Publisher, 2024)
This study discusses the strategy for overcoming drug crimes by children in the digital era so that the government pays attention to the problem of drug abuse, by implementing Law Number 22 of 1997 concerning Narcotics, which gives consequences to anyone who abuses drugs can undergo criminal penalties, if they meet the demands in accordance with the articles contained in the law (BPHN, 1997). The purpose of this study is to be able to Repeated criminal acts or recidivism to be given more attention in handling drug crime cases, which are a familiar phenomenon in Indonesia, especially narcotics recidivism, many factors cause someone to repeat their crime, such as economic interests, narrow job opportunities, low levels of education. The author will conduct research using qualitative methods and data obtained from interviews, observations, and literature studies. Based on the results of research conducted on prisoners, previous research, documents, and discussions conducted by the author. Insights used in children information from the BNN: Based on the BNN annual report, the dominance of opiate use among young people is increasing. It is reported that around 10% of teenagers have used drugs by 2023. Source: National Narcotics Agency (BNN).